Level and predictors of adjustment of selected seminarians - Justalero, Nilo M. (Animo Repository, 1996)
This study identifies and correlates the level of adjustment and its predictors among seminarians. Forty-four seminarians who were in their theological studies participated in the study. Twenty of them were considered as regular seminarians, while twenty-four were considered as late-vocation seminarians. They belonged to the young and middle adulthood stage with ages ranging from 22 to 39 years. They stayed at the San Carlos Pastoral Formation Complex, Makati City. Four instruments were used. These were the (a) Personal Information Questionnaire, (b) Spiritual Well-being Scale, (c) Psychological Separation Inventory, and (d) Panukat ng Kabuuang Pagkatao. The respondents who were either regular or late-vocation seminarians had the following characteristics:1. They stayed from 1-10 years in the seminary 2. They were usually third in birth order and,3. They came from an average to a large-sized family. Regression analysis showed that the best predictors of adjustments were their spiritual well-being and their conflicting independence from their mothers. This was measured by the MCI Scale of Psychological Separation Inventory. They were average in their level of adjustments. This suggested that the respondents were in the process of adjusting to their current life situation.